2008
DOI: 10.1007/s11104-008-9776-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of proton budgets in soils of cropland and adjacent forest in Thailand and Indonesia

Abstract: Continuous cultivation has the potential to accelerate soil acidification. The influence of cultivation on soil acidification was evaluated by calculating proton budget in a soil-vegetation system including solute leaching, vegetation uptake and organic matter decomposition in cropland and adjacent forest in Thailand and Indonesia. In the forests, excess cation accumulation in wood (2.1-3.8 kmol c ha −1 year −1 ) has contributed to soil acidification at the rate of 0.004 mol c for production of 1 mol carbon. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
6
43
0
Order By: Relevance
“…Factors controlling intra-stand spatial variability of annual TIN leaching from litter and surface soil layers TIN input via rainfall and throughfall in this study (0.64 and 0.67 g N m À2 year À1 , respectively) were lower than in temperate forests in Europe and North America (e.g., 1.0-3.3 and 1.3-5.9 g N m À2 year À1 ; Gundersen et al, 1998) and in subtropical forests in South China (3.4 and 2.5-3.5 g N m À2 year À1 ; Fang et al, 2008) but were comparable to levels observed in a tropical rainforest in Costa Rica (0.6 and 1.7 g N m À2 year À1 ; Schwendanmann and Veldkamp, 2005) and in tropical montane forests in northern Thailand (0.87 g N m À2 year À1 in throughfall; Fujii et al, 2009) and Puerto Rico (0.19 and 0.35 g N m À2 year À1 ; McDowell, 1998). We propose that the relatively low level of N input via throughfall in tropical areas, including in this study, may be due to low atmospheric N deposition (with the exception of the forests of South China).…”
Section: 2supporting
confidence: 55%
“…Factors controlling intra-stand spatial variability of annual TIN leaching from litter and surface soil layers TIN input via rainfall and throughfall in this study (0.64 and 0.67 g N m À2 year À1 , respectively) were lower than in temperate forests in Europe and North America (e.g., 1.0-3.3 and 1.3-5.9 g N m À2 year À1 ; Gundersen et al, 1998) and in subtropical forests in South China (3.4 and 2.5-3.5 g N m À2 year À1 ; Fang et al, 2008) but were comparable to levels observed in a tropical rainforest in Costa Rica (0.6 and 1.7 g N m À2 year À1 ; Schwendanmann and Veldkamp, 2005) and in tropical montane forests in northern Thailand (0.87 g N m À2 year À1 in throughfall; Fujii et al, 2009) and Puerto Rico (0.19 and 0.35 g N m À2 year À1 ; McDowell, 1998). We propose that the relatively low level of N input via throughfall in tropical areas, including in this study, may be due to low atmospheric N deposition (with the exception of the forests of South China).…”
Section: 2supporting
confidence: 55%
“…The unsaturated hydraulic conductivity and soil water pressure heads at depths of 5, 15 and 30 cm were estimated using the saturated hydraulic conductivity, water retention curves of soil and volumetric water content monitored at each depth at 30-minute intervals (Mualem and Dagan 1978;Van Genuchten, 1980). Details of the calculations of soil water fluxes are presented previously (Fujii et al, 2008(Fujii et al, , 2009). The soil water fluxes for each month were calculated by summing the halfhourly soil water fluxes.…”
Section: Calculation Of Fluxes Of Dissolved Organic Carbon Al and Fementioning
confidence: 99%
“…According to proton budget analysis in the BS soil (Fujii et al, 2009), protons were produced in the O horizon owing to the dissociation of one acidic functional group per 11.5 carbon atoms of the DOC. DOC-associated proton generation accounts for 50% of total proton generation in the O horizon of the BS soil and contributes to soil acidification and eluviation of Al and Fe, along with the other proton sources as acidic deposition, nitrification, dissociation of carbonic acid and excess cation uptake by vegetation.…”
Section: Implication For Pedogenetic Processesmentioning
confidence: 99%
“…Soil acidification is an ongoing pedogenetic process driven by proton sources such as acidic deposition, nitrification, the dissociation of carbonic and organic acids, and excess cation uptake by vegetation in forest ecosystems (Van Breemen et al, 1983;Binkley and Richter, 1987;Fujii et al, 2009a). Proton sources play an essential part in mineral weathering reactions, which are responsible for long-term change in soils at a pedological time scale (Ugolini and Sletten, 1991).…”
Section: Introductionmentioning
confidence: 99%